(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2025)
This article examines the implementation of culturally responsive pedagogy (CRP) in English for Specific Purposes (ESP) teaching, recognizing ESP as a learner-centric approach tailored to individual needs. Despite this acknowledgment, the optimal methods for achieving learner goals remain elusive. Academics stress the need for a personalized approach, emphasizing the teacher’s awareness and ability to select or create suitable methodologies. Within the context of a Greek classroom influenced by Katsara’s (2021) facilitator-oriented model, the study utilized the Read, Ask, and Paraphrase (RAP) strategy by Schumaker et al. (1984) for a seminar on global citizenship principles in business. Evaluation through reflection journals of 39 Greek business students revealed their high satisfaction, highlighting the impact of power dynamics on instructional delivery. Students appreciated the topic’s relevance, the facilitative nature of teaching materials, and specific academic writing skills. Suggestions for improvement included more guidelines and exploration of specialized business topics, underscoring the teacher’s role as a facilitator. The paper proposes preliminary pedagogical implications for a foreign language policy aligned with the approach used in the study